Identifikasi Bakteri Probiotik pada Saluran Pencernaan Ikan Semah (Tor Sp.) - Andriyanto Andriyanto; Eni Yulianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to isolate and identify the type of probiotic potential bacteria in the digestive tract of semah fish (Tor sp.) originating from Batang Merangin river, Jambi Province. Semah fish sampling was carried out at three observation stations namely Batang Merangin river watershed, Station I was located in Talang Kawo Village, station II was located in Guguk Village and station III was located in Muara Emat Village. In Station I, 4 fish were obtained, station II obtained 5 fish and station III obtained 2 fish. The total length of the fish obtained ranges from 16cm-22 cm. Of all the samples of semah fish obtained, all are species of Tor tambroides. Conclusion, the results of isolation and identification of potential probiotic bacteria in the digestive tract of fish (Tor tambroides) living in the Batang Merangin river obtained two genus of probiotic potential bacteria namely Bacillus sp. and Alcaligenes sp. Keywords: Semah Fish, Isolation, Identification, Probiotics